Measurement of TLR-Induced Macrophage Spreading by Automated Image Analysis: Differential Role of Myd88 and MAPK in Early and Late Responses - Wenzel, Jens; Held, Christian; Palmisano, Ralf; Teufel, Stefan; David, Jean-Pierre; Wittenberg, Thomas; Lang, Roland (Frontiers in Physiology, 2011)
Sensing of infectious danger by Toll-like receptors (TLR) on macrophages causes not only a reprogramming of the transcriptome but also changes in the cytoskeleton important for cell spreading and motility. Since manual determination of cell contact areas from fluorescence microscopy pictures is very time consuming and prone to bias, we have developed and tested algorithms for automated measurement of macrophage spreading. The two-step method combines identification of cells by nuclear staining with DAPI and cell surface staining of the integrin CD11b. Automated image analysis correlated very well with manual annotation in resting macrophages and early after stimulation, whereas at later time points the automated cell segmentation algorithm and manual annotation showed slightly larger variation. The method was applied to investigate the impact of genetic or pharmacological inhibition of known TLR signaling components. Deificiency in the adapter protein Myd88 strongly reduced spreading activity at the late time points, but had no impact early after LPS stimulation. A similar effect was observed upon pharmacological inhibition of MEK1, the kinase activating the MAPK ERK1/2, indicating that ERK1/2 mediates Myd88-dependent macrophages spreading. In contrast, macrophages lacking the MAPK p38 were impaired in the initial spreading response but responded normally 8 – 24 h after stimulation. The dichotomy of p38 and ERK1/2 MAPK effects on early and late macrophage spreading raises the question which of the respective substrate proteins mediate(s) cytoskeletal remodeling and spreading. The automated measurement of cell spreading described here increases the objectivity and greatly reduces the time required for such investigations and is therefore expected to facilitate larger through-put analysis of macrophage spreading, e.g. in siRNA knockdown screens.